Recent advances in the effective removal of hazardous pollutants from wastewater by using nanomaterials—A review - Chahar, Mamta; Khaturia, Sarita; Singh, Har Lal; Solanki, Vijendra Singh; Agarwal, Neha; Sahoo, Dipak Kumar; Yadav, Virendra Kumar; Patel, Ashish (Frontiers in Environmental Science, 2023)
Environmental nanotechnology has developed rapidly over the past few decades due to the fast advancement of nanotechnology and nanomaterials (NMs). Due to their nanoscale size, NMs are receiving an immense amount of attention in research and development all over the world. This is because their nano size has led to better catalysis, high reactivity, and high adsorption capacity. In the area of wastewater treatment, nanotechnology has significant potential in the improvement of performance and efficiency of decontamination of water and more effectively, it provides a sustainable way to keep water supplies safe. Numerous studies have found that the removal of harmful components from wastewater by employing nanoparticles in conjunction with a variety of treatment methods is effective. The purpose of the current investigation is to conduct a review on the envisioned applications of various NMs in the treatment of wastewater. These NMs include carbonaceous NMs, metal-containing nanoparticles, and nanocomposites, all of which will be reviewed and highlighted in depth.Carbon nanotubes, Graphene, Nanocomposites, Nanomaterials, Wastewater etc), physical vapor deposition (PVD), and material synthesis with template assistance, can be used to create synthetic NPs. Materials can suddenly display radically different properties when scaled down to the nanoscale from what they do at the macroscale (Saleh et al., 2022b). For instance, opaque compounds can become transparent (like copper), inert substances can act as catalysts (like platinum), stable substances can catch fire (like aluminum), solids can convert into liquids at normal temperature (like gold), and insulators can act as conductors (like silicon) (Puri et al., 2021)(Horikoshi andSerpone, 2013).Due to their nanoscale size (⁓100 nm), NMs are mechanically and electrically showing a different behavior, and some of their optical and magnetic properties also differ from conventional materials (Alshammari et al., 2020;Modi et al., 2022). In the last past decades, many researchers are devoted to NMs preparation and also optimize them for information processing, machine learning (Jia et al.,